Natural Synthesis of Silver Nanoparticles from Grape Fruit Juice and Estimation of Antimicrobial Activity - Fatima, Mehreen; Quraishi, Azra; Akram, Maida (BioScientific Review, 2021)
Silver has been known for its antimicrobial activity for a very long time. The formulation of silver particles that range from 1-100nm in size makes it even more potent in terms ofinducingantimicrobial effects.Green chemistry has started toinfluencethe field of biochemical research. Silver Nanoparticles(Ag-NPs)synthesized through the green synthesis method provide a cheap and ecofriendlywayof nanoparticle preparation. Theaim of the current study is to prepare the green synthesis of Ag-NPsusing tomato juice as a reducing and capping agent and the evaluation of its antimicrobial activity. The stability and conformation ofAg-NPs was determined usingUV-visible spectroscopy. The antimicrobial activity of synthesizedAg-NPs was determined against E.coli DH5α.Ultraviolet spectroscopic analysis offered peak at 400 nm whichindicatedthe production of Ag-NPs of adequate size. E.coli DH5αdecreasedconsiderably upon the introduction of Ag-NPsto the bacterial inoculum. On increasing the concentration of Ag-NPs,an increase in the zone of inhibition was recorded. For 70μg/ml of Ag-NPs the zone of inhibition was 0.5 cm, while 0.6 cm, 0.7 cm and 0.7cm wererecorded for 100μg/ml, 150μg/ml and 200μg/ml of Ag-NPs,respectively. The efficacy of the antimicrobial activity of Ag-NPsderived from tomato juice proves its potential use in pharmaceutical and medicinal industries for the synthesis of nanomedicine. Keywords: antimicrobial effect, grapefruit, green chemistry, nanomedicine, silver nanoparticles (Ag-NPs) Copyright (c) The Authors